Hypostomus hermanni redescription and a new species of Hypostomus (Siluriformes: Loricariidae) from Upper Paraná River basin, Brazil - Dias,Angelica Corrêa (2021)
Abstract A redescription of Hypostomus hermanni is presented herein along with the description of a new species of Hypostomus, which is apparently endemic to the Ivaí River basin, a tributary of the Upper Paraná River basin, Brazil. Hypostomus hermanni is diagnosed from congeners mainly by having: usually large black blotches on body and fins; absence of keels on compound pterotic, on pre-dorsal plates, and on lateral series of bony plates; by having parieto-supraoccipital and predorsal region flat; and by having less than 46 teeth per each premaxilla or dentary ramus. The new species is distinguished from congeners mainly for lacking conspicuous blotches, parieto-supraoccipital non-carinate, and villiform bicuspid teeth.